Web-Based User Center Design - Siti Sufaidah; Zuhal Ahmadi (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Web-Based User Center Design is an e-commerce application that is engaged in conventional buying and selling serving the manufacture of t-shirts, jackets, shirts, uniforms, etc. With an existing design or customizing an existing design, the purpose of making a Web-Based User Center Design application is to build a special e-commerce application in the convection field for convection entrepreneurs, as for the benefits of making this e-commerce application, which is expected can make it easier to sell and promote its products so that it can increase turnover for convection entrepreneurs.